Assessment of uncertainties in the response of the African monsoon precipitation to land use change simulated by a regional model - Samson Hagos; L. Ruby Leung; Yongkang Xue; Aaron Boone; Fernando de Sales; Naresh Neupane; Maoyi Huang; Jin-Ho Yoon (Climate Dynamics, 2014)

Cytotoxicity studies of semi-synthetic derivatives of theveside derived from the aqueous extract of leaves of ‘suicide tree’ Cerbera odollam - Jaggaiah N. Gorantla; Jamsheena Vellekkatt; Lekshmi R. Nath; Ruby John Anto; Ravi S. Lankalapalli (Natural Product Research, 2014)

Non‐native acylated homoserine lactones reveal that LuxIR quorum sensing promotes symbiont stability - Sarah V. Studer; Julia A. Schwartzman; Jessica S. Ho; Grant D. Geske; Helen E. Blackwell; Edward G. Ruby (Environmental Microbiology, 2014)
Summary Quorum sensing, a group behaviour coordinated by a diffusible pheromone signal and a cognate receptor, is typical of bacteria that form symbioses with plants and animals. LuxIR ‐type N ‐acyl L‐homoserine ( AHL ) quorum sensing is common in Gram‐negative Proteobacteria , and many members of this group have additional quorum‐sensing networks. The bioluminescent symbiont V ibrio fischeri encodes two AHL signal synthases: AinS and LuxI . AinS ‐dependent quorum sensing converges with LuxI ‐dependent quorum sensing at the LuxR regulatory element. Both AinS ‐ and LuxI ‐mediated signalling are required for efficient and persistent colonization of the squid host, E uprymna scolopes . The basis of the mutualism is symbiont bioluminescence, which is regulated by both LuxI ‐ and AinS ‐dependent quorum sensing, and is essential for maintaining a colonization of the host. Here, we used chemical and genetic approaches to probe the dynamics of LuxI ‐ and AinS ‐mediated regulation of bioluminescence during symbiosis. We demonstrate that both native AHLs and non‐native AHL analogues can be used to non‐invasively and specifically modulate induction of symbiotic bioluminescence via LuxI ‐dependent quorum sensing. Our data suggest that the first day of colonization, during which symbiont bioluminescence is induced by LuxIR , is a critical period that determines the stability of the V . fischeri population once symbiosis is established.

Molecular cloning and characterization of genistein 4′-O-glucoside specific glycosyltransferase from Bacopa monniera - Ruby; R. J. Santosh Kumar; Rishi K. Vishwakarma; Somesh Singh; Bashir M. Khan (Molecular Biology Reports, 2014)

Genetic relationships among a collection of Musa germplasm by fluorescent-labeled SRAP - Ruby Valdez-Ojeda; Andrew James-Kay; José Roberto Ku-Cauich; Rosa María Escobedo-GraciaMedrano (Tree Genetics & Genomes, 2014)

A modeling study of coastal inundation induced by storm surge, sea-level rise, and subsidence in the Gulf of Mexico - Zhaoqing Yang; Taiping Wang; Ruby Leung; Kathy Hibbard; Tony Janetos; Ian Kraucunas; Jennie Rice; Benjamin Preston; Tom Wilbanks (Natural Hazards, 2014)

Exercise-induced oxidative stress and hypoxic exercise recovery - Christopher Ballmann; Graham McGinnis; Bridget Peters; Dustin Slivka; John Cuddy; Walter Hailes; Charles Dumke; Brent Ruby; John Quindry (European Journal of Applied Physiology, 2014)

Biopharmaceutical considerations and characterizations in development of colon targeted dosage forms for inflammatory bowel disease - Rajkumar Malayandi; Phani Krishna Kondamudi; P. K. Ruby; Deepika Aggarwal (Drug Delivery and Translational Research, 2014)

Features governing symbiont persistence in the squid–vibrio association - Eric J. Koch; Tim Miyashiro; Margaret J. McFall‐Ngai; Edward G. Ruby (Molecular Ecology, 2014)
Experimental studies of the interaction between host and symbiont in a maturing symbiotic organ have presented a challenge for most animal–bacterial associations. Advances in the rearing of the host squid Euprymna scolopes have enabled us to explore the relationship between a defect in symbiont light production and late‐stage development ( e.g . symbiont persistence and tissue morphogenesis) by experimental colonization with specific strains of the symbiont Vibrio fischeri . During the first 4 weeks postinoculation of juvenile squid, the population of wild‐type V. fischeri increased 100‐fold; in contrast, a strain defective in light production (Δ lux ) colonized normally the first day, but exhibited an exponential decline to undetectable levels over subsequent weeks. Co‐colonization of organs by both strains affected neither the trajectory of colonization by wild type nor the decline of Δ lux levels. Uninfected animals retained the ability to be colonized for at least 2 weeks posthatch. However, once colonized by the wild‐type strain for 5 days, a subsequent experimentally induced loss of the symbionts could not be followed by a successful recolonization, indicating the host's entry into a refractory state. However, animals colonized by the Δ lux before the loss of their symbionts were receptive to recolonization. Analyses of animals colonized with either a wild‐type or a Δ lux strain revealed slight, if any, differences in the developmental regression of the ciliated light‐organ tissues that facilitate the colonization process. Thus, some other feature(s) of the Δ lux strain's defect also may be responsible for its inability to persist, and its failure to induce a refractory state in the host.

Eddy fluxes and sensitivity of the water cycle to spatial resolution in idealized regional aquaplanet model simulations - Samson Hagos; L. Ruby Leung; William I. Gustafson; Balwinder Singh (Climate Dynamics, 2014)